2010
DOI: 10.1111/j.1750-3639.2009.00340.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation and Transcriptional Downregulation of the TIMP3 Gene is Associated with Allelic Loss on 22q12.3 and Malignancy in Meningiomas

Abstract: The gene for the tissue inhibitor of metalloproteinase 3 (TIMP3) on 22q12.3 had been reported to be inactivated by promoter methylation in various types of cancers, with controversial findings in meningiomas. We performed direct sodium bisulfite sequencing in a series of 50 meningiomas, including 27 benign meningiomas [World Health Organization (WHO) grade I], 11 atypical meningiomas (WHO grade II) and 12 anaplastic meningiomas (WHO grade III), and found hypermethylation of TIMP3 in 67% of anaplastic meningiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 26 publications
2
60
0
1
Order By: Relevance
“…Hypermethylation of the 22q12 gene TIMP3 and subse quent transcriptional downregulation (gene silencing) has been identified as a marker for an aggressive, high-grade meningioma phenotype. 4,49 Although there is some minor disagreement in the literature, Grade I tumors have been found to have significantly less aberrant methylation at TIMP3 than Grade II or III meningiomas.…”
Section: Tumor Suppressor Genesmentioning
confidence: 99%
“…Hypermethylation of the 22q12 gene TIMP3 and subse quent transcriptional downregulation (gene silencing) has been identified as a marker for an aggressive, high-grade meningioma phenotype. 4,49 Although there is some minor disagreement in the literature, Grade I tumors have been found to have significantly less aberrant methylation at TIMP3 than Grade II or III meningiomas.…”
Section: Tumor Suppressor Genesmentioning
confidence: 99%
“…TIMP3 has been proposed as a tumor suppressor in several human cancer types. Silencing of TIMP3 through promoter hypermethylation has been associated with poor prognosis in a range of human cancers including kidney, brain, colon (Bachman et al, 1999), non-small cell lung (Zochbauer-Muller et al, 2001) and meningiomas (Barski et al, 2010). Loss of TIMP3 expression, through loss of heterozigosity on chromosome 22q, is frequently observed in various cancers, such as secondary glioblastoma (Nakamura et al, 2005) and clear renal cell carcinomas (Masson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…22 Research into altered methylation of genes related to meningioma has revealed hypermethylation of purported antiproliferation genes in atypical and anaplastic meningiomas. 17 Several reports have shown that underexpression through hypermethylation of the MGMT, 2 TIMP3, 3 and NDRG2 18 genes is associated with malignant potential or progression. A genome-wide methylation study described 3 clusters of methylation patterns based on comparing WHO Grade I and II meningiomas with normal meninges.…”
mentioning
confidence: 99%